A household survey to assess community knowledge, attitude and practices on malaria in a rural population of Northern India - Rajiv Kumar Gupta; Sunil Kumar Raina; Tajali N Shora; Rayaz Jan; Renu Sharma; Shahid Hussain (Journal of Family Medicine and Primary Care, 2016)
Introduction: An extensive search on PubMed reveals very little in terms of evidence regarding the current knowledge, attitude, and practices (KAP) of the population in general and rural population, in particular, in this part of the country. Therefore, a study was conducted with the aim to assess the communities′ knowledge of malaria transmission, recognition of signs and symptoms, treatment seeking. Materials and Methods: A stratified two-stage design was used to conduct a house-to-house survey using a semi-structured questionnaire in RS Pura block of Jammu District of Jammu and Kashmir State in North India. Results: A total of 300 households were included in the study. However, data on 4 households was found to be incomplete at the time of analysis and, therefore, were excluded. Out of 296 study participants interviewed 65.5% were males, while 34.5% females. All of the study participants (100%) had heard of malaria, and the main source of their information was television/newspaper. 92.5% of the study population considered malaria to be a serious health problem, thus reflecting their attitude to the disease. Regarding practices, 71.6% of the study participants preferred going to doctors at government hospitals for malaria treatment, and 56% were willing to seek medical help in <24 h in case of a child has a febrile episode. Conclusions: Results revealed that KAP among respondents were reasonably good and key sociocultural, and related indicators need to be identified as a part of malaria elimination strategy.